Characterization of an exopolysaccharide produced by Lactobacillus plantarum YW11 isolated from Tibet Kefir. (10th July 2015) - Wang, Ji; Zhao, Xiao; Tian, Zheng; Yang, Yawei; Yang, Zhennai
Highlights: Physicochemical, rheological properties, structural characterization, and microstructure of the EPS from L. plantarum are reported. The EPS produced by L. plantarum YW11 is a promising candidate for exploitation in food industry. The EPS has higher viscosity in skim milk, at lower temperature, or at acidic pH. Unlike reported before, the EPS from L. plantarum YW11 shows a highly branched and porous structure. The EPS has high thermal stability. Abstract: An exopolysaccharide (EPS)-producing strain YW11 isolated from Tibet Kefir was identified as Lactobacillus plantarum, and the strain was shown to produce 90 mg L −1 of EPS when grown in a semi-defined medium. The molecular mass of the EPS was 1.1 × 10 5 Da. The EPS was composed of glucose and galactose in a molar ratio of 2.71:1, with possible presence of N -acetylated sugar residues in the polysaccharide as confirmed by NMR spectroscopy. Rheological studies showed that the EPS had higher viscosity in skim milk, at lower temperature, or at acidic pH. The viscous nature of the EPS was confirmed by observation with scanning electron microscopy that demonstrated a highly branched and porous structure of the polysaccharide. The atomic force microscopy of the EPS further revealed presence of many spherical lumps, facilitating binding with water in aqueous solution. The EPS had a higher degradation temperature (287.7 °C), suggesting high thermal stability of the EPS.